2010
DOI: 10.1021/es101073p
|View full text |Cite
|
Sign up to set email alerts
|

Photoreactivity of Carboxylated Single-Walled Carbon Nanotubes in Sunlight: Reactive Oxygen Species Production in Water

Abstract: Very limited information exists on transformation processes of carbon nanotubes in the natural aquatic environment. Because the conjugated pi-bond structure of these materials is efficient in absorbing sunlight, photochemical transformations are a potential fate process with reactivity predicted to vary with their diameter, chirality, number and type of defects, functionalization, residual metal catalyst and amorphous carbon content, and with the composition of the water, including the type and composition of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
136
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(147 citation statements)
references
References 35 publications
10
136
1
Order By: Relevance
“…Aqueous colloidal dispersions of bare and functionalized CNTs have been reported to generate ROS including singlet oxygen, superoxide anion, and hydroxyl radicals in light within the solar spectrum under oxic conditions. Purified CNTs were found to be generally more photoactive, producing singlet oxygen and superoxide, while little or no photoactivity was observed for raw CNTs 22, 23, 24. CNTs can also act as scavengers of hydroxyl or superoxide radicals,74, 75, 76, 77 or undergo photochemical transformations (e.g., decarbonilation) as in the case of oxidized multiwalled CNTs 24…”
Section: Origin Of Photoactivity Of Nanoporous Carbonsmentioning
confidence: 96%
See 1 more Smart Citation
“…Aqueous colloidal dispersions of bare and functionalized CNTs have been reported to generate ROS including singlet oxygen, superoxide anion, and hydroxyl radicals in light within the solar spectrum under oxic conditions. Purified CNTs were found to be generally more photoactive, producing singlet oxygen and superoxide, while little or no photoactivity was observed for raw CNTs 22, 23, 24. CNTs can also act as scavengers of hydroxyl or superoxide radicals,74, 75, 76, 77 or undergo photochemical transformations (e.g., decarbonilation) as in the case of oxidized multiwalled CNTs 24…”
Section: Origin Of Photoactivity Of Nanoporous Carbonsmentioning
confidence: 96%
“…In 2009, Luo et al reported the self‐photoactivity of carbon nanotubes under visible light, attributing the behavior to the presence of structural defects and vacancies 21. Later, other authors reported the ability of aqueous suspensions of carbon nanotubes to generate reactive oxygen species (ROS) including singlet oxygen, superoxide anion, and hydroxyl radicals upon illumination with light within the solar spectrum 22, 23, 24…”
Section: Introductionmentioning
confidence: 99%
“…However, degradation processes of these materials have not been fully investigated, so altering the composite material and releasing CNT are difficult to evaluate [53]. First results indicate that CNT can be released on photochemical degradation (process 1) of CNT-containing composites [80,81]. The PM-ENM composite material will be subjected to UVA/B radiation and abrasive forces while in use that will weaken molecular bonds and release CNT over an extended period.…”
Section: Case Study 5: Carbon Nanotubes In Compositesmentioning
confidence: 99%
“…The PM-ENM composite material will be subjected to UVA/B radiation and abrasive forces while in use that will weaken molecular bonds and release CNT over an extended period. These released CNT (PW-ENM) would make their way into waste water treatment plants or be directly deposited into environmental compartments where they would undergo transformation by photochemistry (process 1) [81], oxidation (process 2), adsorption of NOM [33] and other organic colloids [34], biotransformation (process 7), and continued abrasive forces (process 8). These transformative processes would change CNT aggregation, dispersability, and interaction with biota in the environmental compartment.…”
Section: Case Study 5: Carbon Nanotubes In Compositesmentioning
confidence: 99%
“…The modest photocatalytic activity of CNTs could be due to the ability of CNTs to produce the reactive oxygen species (ROSs) under irradiation. 41 Apparently, the photocatalytic activity of Ag/AgBr-CNTs is markedly improved by the loading of AgBr onto the CNTs surface. The photocatalytic removal of TBP was also performed using Ag/AgCl-CNTs and Ag/AgI-CNTs as photocatalysts ( Figure 7b).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%